Crowdfunding innovations. (2016) - Yablonsky, Sergey
The research focuses on crowdfunding innovations for financial services. This paper aims to collect and analyse the quality data regarding the current status and prospective evolution of crowdfunding. Empirical research on crowdfunding innovations has increased, providing a descriptive narrative on the current situations across different countries. However, theoretical efforts to explain global crowdfunding are so far inexistent. The scope of this paper is to provide an ontology/taxonomy conceptual models for explaining crowdfunding innovations that take into account ecosystem and business models of crowdfunding. The proposed models are the first of this kind in providing a set of concepts and relations in this dynamic subject area. The study offers classification and examination of the current status of crowdfunding and proposes definition of the crowdfunding multi-sided platform and develops research framework for crowdfunding platforms business models analysis and comparison.